OsSHI1 Regulates Plant Architecture Through Modulating the Transcriptional Activity of IPA1 in Rice. Issue 5 (25th March 2019) - Duan, Erchao; Wang, Yihua; Li, Xiaohui; Lin, Qibing; Zhang, Ting; Wang, Yupeng; Zhou, Chunlei; Zhang, Huan; Jiang, Ling; Wang, Jiulin; Lei, Cailin; Zhang, Xin; et al.
Abstract : OsSHI1 represses the DNA binding activity of IPA1 to regulate plant architecture in rice. Abstract: Tillering and panicle branching are important determinants of plant architecture and yield potential in rice ( Oryza sativa ). IDEAL PLANT ARCHITECTURE1 ( IPA1 ) encodesSQUAMOSA PROMOTER BINDING PROTEIN-LIKE14, which acts as a key transcription factor regulating tiller outgrowth and panicle branching by directly activating the expression of O. sativa TEOSINTE BRANCHED1 ( OsTB1 ) and O. sativa DENSE   AND ERECT PANICLE1 ( OsDEP1 ), thereby influencing grain yield in rice. Here, we report the identification of a rice mutant named shi1 that is characterized by dramatically reduced tiller number, enhanced culm strength, and increased panicle branch number. Map-based cloning revealed that O. sativa SHORT INTERNODES1 ( OsSHI1 ) encodes a plant-specific transcription factor of the SHI family with a characteristic family-specific IGGH domain and a conserved zinc-finger DNA binding domain. Consistent with the mutant phenotype, OsSHI1 is predominantly expressed in axillary buds and young panicle, and its encoded protein is exclusively targeted to the nucleus. We show that OsSHI1 physically interacts with IPA1 both in vitro and in vivo. Moreover, OsSHI1 could bind directly to the promoter regions of both OsTB1 and OsDEP1 through a previously unrecognized cis-element (T/GCTCTAC motif). OsSHI1 repressed the transcriptional activation activity of IPA1 by affecting its DNA binding activity toward the promoters of both OsTB1 and OsDEP1, resulting in increased tiller number and diminished panicle size. Taken together, our results demonstrate that OsSHI1 regulates plant architecture through modulating the transcriptional activity of IPA1 and provide insight into the establishment of plant architecture in rice.